New perspectives into the chemical characterization of Sida acuta Burm. f. extracts with respect to its anti-cancer, antioxidant and enzyme inhibitory effects - Uysal, Sengul; Gevrenova, Reneta; Sinan, Kouadio Ibrahime; Bayarslan, Aslı Ugurlu; Altunoglu, Yasemin Celik; Zheleva-Dimitrova, Dimitrina; Ak, Gunes; Baloglu, Mehmet Cengiz; Etienne, Ouattara Katinan; Lobine, Devina; Mahomoodally, Mohamad Fawzi; Zengin, Gokhan (Elsevier BV, 2021)
Abstract The chemical components, in vitro antioxidant capacities and enzyme inhibitory effects of dichloromethane (DCM), ethyl acetate (EA), methanol (MeOH) and water extracts of the medicinal plant, Sida acuta Burm. f. were evaluated. The individual phenolic components were assessed via ultra-high-performance liquid chromatography-high-resolution mass spectrometry (UHPLC-HRMS). In terms of chemical composition, phenolics (hydroxybenzoic and hydroxycinnamic acids) and flavonoids were identified as main groups. The antioxidant capacities were evaluated using a panoply of cell-free bioassays and the enzymatic inhibitory potentials against key enzymes involved in human diseases were also determined. The water extract exhibited the strongest scavenging abilities on DPPH (IC50: 1.05 mg/mL) and ABTS (IC50: 1.02 mg /mL). The best cholinesterase inhibitory abilities were observed with the methanol extract (IC50: 0.51 and 0.52 mg/mL for AChE and BChE, respectively), while DCM exhibited the strongest α-amylase (IC50: 1.21 mg/mL) and α-glucosidase (IC50: 0.62 mg/mL) inhibitory effects. The anti-cancer effects of methanol and water extracts were tested on human breast cancer cells, MDA-MB-231, and the methanol extract showed the best anti-cancer effect with an IC50 value of 102.4 μg/mL. In conclusion, the experimental data have demonstrated promising pharmacological activities of S. acuta extracts obtained using different solvents, thereby providing a scientific basis for the validation of the traditional medicinal uses of this plant.
Keywords: 3. Good health